Evaluating predictors of invasive candidiasis in patients with and without candidemia on micafungin. Issue 1 (2nd January 2018) - Carr, Amy; Colley, Peter; Berhe, Mezgebe; Nguyen, Hoa L.
ABSTRACT: Numerous risk factors have been linked to invasive candidiasis; however, they are nonspecific and often trigger empiric antifungal therapy in a large number of patients. Identification of more precise predictors could promote judicious use of empiric echinocandins. In this retrospective review, 127 patients with blood cultures positive for Candida spp. were compared to a randomly selected cohort of 134 patients on empiric micafungin for ≥3 days and with blood cultures negative for Candida spp. Factors associated with candidemia included total parenteral nutrition (TPN; 26.0% vs 15.7%, P = 0.040), multifocal Candida colonization (23.6% vs 3.0%, P < 0.001), and positive 1, 3-β-d -glucan assay (95.0% vs 35.0%, P < 0.001). Patients without candidemia on empiric micafungin were more likely to receive antibiotic therapy in the previous 10 days (55.9% vs 79.9%, P < 0.001) and to be taking immunosuppressive medications (11.0% vs 30.6%, P < 0.001). Receipt of TPN (odds ratio [OR] = 2.07, 95% confidence interval [CI], 1.02–4.21), severe sepsis (OR = 2.20, 95% CI, 1.00–4.83), and multifocal Candida colonization (OR = 13.87, 95% CI, 4.43–43.37) were independently associated with candidemia in the multivariable logistic regression model. Therefore, the absence of these risk factors, especially in conjunction with a negative 1, 3-β-d -glucan assay, may be used to recommend de-escalation of empiric micafungin therapy.